The Relationship of the Risk of Falls with the Features of Cognitive Function and Emotional Status (Fear of Falls) in Older People - I. A. Samkova; V. N. Larina; S. E. Кozyrev; N. K. Runihina (SINAPS LLC, 2022)
Objective. To assess the frequency of falls, the relationship between fear of falling and the risk of falls in people aged 60 years and older. Material and methods. The open cross-sectional study included 51 outpatients (49 women, 2 men) aged 61 to 90 [70 (67; 75)] years. A conventional physical examination, clinical and biochemical blood tests, screening for fragility (the "Age is not a hindrance" questionnaire), the risk of falls (history, the "Get up and go" test), fear of falls ("Short scale for assessing the fear of falls", "Scale of effectiveness falls"), assessment of cognitive function (CF) - Montreal scale of cognitive assessment - MoCa-test). Results. A high risk of senile asthenia was found in 38 %, preasthenia - in 31 %, a history of falls - in 75 %, fear of falls - in 78 %, impaired CF - in 49 % (MOCA 24.3±2.9 points) of patients. An association was found between fear of falls and history of falls (odds ratio [OR] 9.92, p=0.003, 95 % confidence interval [CI] 2.20-44.63), 2 or more comorbidities (OR 10.86, p=0.013, 95 % CI 1,66- 71,09); between the "Get up and go" test for more than 10 seconds and MOCA less than 25 points (OR 8.57, p=0.001, CI 2.4-30.3); scores less than 25 on the Fall Effectiveness Scale and MOCA (OR 5.6, p=0.018, CI 1.34-23.36). The optimal value of the "Get up and walk" test for predicting falls was 10.5 seconds or more (area under the curve 0.753±0.083, p=0.019), the MOCA test was 24.5 points or less (area under the curve 0.792±0.065, p <0.001); the fall effectiveness scale for predicting fear of falls - 72.5 points or more (area under the curve 0.743±0.092, p=0.014); test "Get up and go" - 9.5 seconds or more (area under the curve 0.708±0.098, p=0.036). Conclusion. Fear of falls was associated with a history of falls, соmorbidity, low functional activity, and a decrease in CF, which confirms the multifactorial origin of the fear of falls in older age and requires consideration in the development of comprehensive treatment and prevention programs.